2021
DOI: 10.5650/jos.ess20157
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on Functional Components, Physicochemical Properties and Antioxidant Activity of <i>Amaranthus Caudatus</i> L. Oils Obtained by Different Solvents Extraction

Abstract: g crude fat, it is found that Amaranthus caudatus L. oil has unique nutritional characteristics e.g., vitamin E, polyphenols, sterols and other trace active components with a potential stronger antioxidant activity than ordinary oils 6,7 . Amaranthus caudatus L. oil contains among others linoleic acid up to 50 , tocopherols 802 mg/ kg , total sterols 2460 mg/100 g and squalene 4.16 g/kg of seed 8,9 . These components have shown remarkable antioxidant activity, benefits to nutrition and cardiovascular system he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The seed germination and initial growth are vulnerable stages dependent on environmental conditions in Amaranthus tricolor L. cv. Valentina and other crop plants (Ashraf et al, 2002;Raja et al, 2020;Hu et al, 2021;Kandel et al, 2021;Novák et al, 2021). The study suggested the pre-sowing treatment of amaranth seeds with growth stimulants to improve the seed quality, increase the biomass, and the effectiveness of seedling defense systems by activating the synthesis of low molecular weight antioxidants.…”
Section: Discussionmentioning
confidence: 99%
“…The seed germination and initial growth are vulnerable stages dependent on environmental conditions in Amaranthus tricolor L. cv. Valentina and other crop plants (Ashraf et al, 2002;Raja et al, 2020;Hu et al, 2021;Kandel et al, 2021;Novák et al, 2021). The study suggested the pre-sowing treatment of amaranth seeds with growth stimulants to improve the seed quality, increase the biomass, and the effectiveness of seedling defense systems by activating the synthesis of low molecular weight antioxidants.…”
Section: Discussionmentioning
confidence: 99%
“…Germination friendliness can be characterized by the term germination rate (Vaseem et al, 2020;Motyleva et al, 2021). Amaranth (Amaranthus hypochondriacus L.) is a heat-loving pseudocereal plant, widely cultivated in tropical and subtropical regions of the world (Hu et al, 2021;Kandel et al, 2021). Amaranth is an annual crop usually sown in early spring in warm countries.…”
Section: Introductionmentioning
confidence: 99%